A primer of international migration: The Latin American experience - Pablo M. Garcia; Eduardo Rodríguez-Montemayor (Inter-American Development Bank (IDB), 2009)
Migration has recently taken an important place in the agenda of many governments around the world. But the phenomenon of international mobility of individuals is not new. Following Massey [2003], the modern history of international migration can be divided into four periods. During the mercantile period, from about 1500 to 1800, world immigration was dominated by flows out of Europe and stemmed from processes of colonization and economic growth under mercantile capitalism.
hdl:11319/2544
Keywords: 330